Constructing Cultural Literacy in Postdigital Higher Education: A Content Analysis of Literature-Based English Course Materials - Resti Amalia; Resty Widyanty (Journal of Science and Education Research, 2026)
The growing discourse of the “postdigital” challenges the assumption that education is merely transitioning toward digitalization, suggesting instead that digital and non-digital practices are now deeply entangled in shaping knowledge production and pedagogical design. Within this context, the meaning and construction of cultural literacy in literature-based English education require renewed examination. This study investigates how cultural literacy is constructed in literature-based English courses in higher education through a postdigital lens. Employing qualitative content analysis, the study analyzes syllabi, reading lists, teaching modules, assessment prompts, and selected digital components from five university-level courses. The analysis focuses on (1) the types of cultural knowledge privileged or marginalized, (2) the modes through which literary texts are delivered and mediated, and (3) the epistemological assumptions underpinning curriculum design in postdigital contexts. The findings indicate that literature is primarily confined to specialized literature courses, while language skills courses emphasize functional communication and rarely incorporate literary texts. In addition, course materials are largely dominated by canonical and globally recognized Anglophone works, with limited inclusion of local or regional literature. Although digital resources expand access to literary materials, their pedagogical integration remains partial. The study argues that postdigital conditions reshape not only the delivery of literary texts but also the ways cultural knowledge is curated and legitimized within university English curricula.